Milrinone in heart failure. Acute effects on left ventricular systolic function and myocardial metabolism. Issue 1 (July 1985) - Timmis, A D; Smyth, P; Monaghan, M; Walker, L; Daly, K; McLeod, A A; Jewitt, D E
Abstract : Milrinone, a new bipyridine compound related to amrinone, is a potent non-adrenergic inotrope in experimental preparations and also shows vasodilator activity. In the present study the haemodynamic and metabolic effects of milrinone were evaluated in 12 patients with congestive heart failure. Milrinone 5 mg given orally produced a sharp reduction in left ventricular end diastolic pressure without significantly affecting stroke volume. The improvement in left ventricular function was due to a combination of vasodilation and positive inotropism. Thus small reductions in blood pressure and systemic vascular resistance were associated with increments in the isovolumic indices of left ventricular function. The relation between left ventricular end systolic pressure and dimension was displaced leftwards and downwards. Only reductions in left ventricular cavity dimension were statistically significant, however. Though myocardial oxygen consumption did not change significantly, it tended to increase whereas lactate consumption tended to decrease. This trend towards oxygen imbalance suggests the need for caution in the use of milrinone in patients with severe coronary artery disease.